The Role of Teachers in Implementing the Reading Literacy Program on students’ Comprehension in Grade III of State Elementary School - Dewanti Amaranggana Wajraprakara; Abdul karim; Nur Asyiah (Universitas Islam Negeri Palopo, 2025)
This study aims to address the main research question: How do teachers play a role in implementing literacy programs to improve the reading comprehension of third-grade students at Plumbon 1 State Elementary School? The research focuses on three aspects: teachers' roles, learning strategies employed, and the supporting and inhibiting factors in literacy program implementation. A qualitative case study approach was employed, involving 15 third-grade students (6 boys and 9 girls) along with their classroom teacher. Data were collected through systematic observations, in-depth interviews, and documentation, and analyzed descriptively. Findings reveal that the literacy program, implemented for 1.5 years, had a positive impact: 80% of students showed high enthusiasm; reading comprehension improved in explicit meaning (73%) but remained low in implicit meaning (47%). Teachers assumed multidimensional roles as facilitators, models, individual guides, evaluators, and collaborators, applying 14 instructional strategies including a daily 15-minute reading routine, differentiated instruction, and the creation of text-rich environments. While the study provides in-depth insights, its limitations include the small sample size and the single-case design, which restrict the generalizability of findings. Nevertheless, the results emphasize that literacy program success requires systemic support from schools, teachers, parents, and home environments. The study implies that other elementary schools can adapt this literacy model by considering contextual factors and student characteristics. Furthermore, it offers a foundational reference for policymakers to enhance systemic support for the School Literacy Movement (GLS), including teacher training, resource allocation, and strategies for parental engagement.